Eco-friendly fabrication of ZnO-TiO2-rGO nanocomposite for efficient adsorption-assisted organic dyes elimination - Md Elias; Ehsanur Rahman; Sonia Akter; Mohammad Awlad Hossain; Rumana A. Jahan; Md Nizam Uddin; Shakhawat H. Firoz (Open Ceramics)
The growing interest in combining the photocatalytic properties of semiconductors like ZnO and TiO2 with the superior electron conduction capabilities of graphene has resulted in the successful synthesis of in-situ reduced graphene oxide (rGO) supported ZnO-TiO2 nanostructures through a simple microwave-assisted synthesis method. X-ray Diffraction Spectroscopy (XRD), Field Emission Scanning Electron Microscope (FESEM), UV–visible spectroscopy (UV–vis), and Fourier Transform Infrared Spectroscopy (FTIR) were employed to characterize structural, morphological and optical properties as well as surface functional groups of the synthesized products. The XRD measurements of our synthesized samples confirm both structural crystallinity and phase purity, while the FTIR analysis verifies the complete reduction of graphene oxide (GO) to reduced graphene oxide (rGO). The synthesized ternary nanocomposite ZnO-TiO2-rGO exhibited a remarkable 100 % adsorption-assisted removal efficiency for 20 mg/L methylene blue (MB) dye under ultraviolet light illumination within 120 min, along with a 56 % dye adsorption removal efficiency in the same time interval. In comparison, pure ZnO showed 0 % adsorption and only 31 % photocatalytic efficiency at the similar condition. Remarkably, the ZnO-TiO2-rGO nanocomposite exhibited exceptional photocatalytic activity mediated by adsorption, achieving complete degradation of MB dye within 5 min under sunlight irradiation. The photocatalytic efficiency and dye adsorption capacity were found to be significantly lower for the anionic dye methyl orange (MO) compared to the cationic MB dye. The study thoroughly investigated the influence of catalyst dose and initial dye concentration on photodegradation. The proposed mechanism indicates that the extensive surface area and numerous active sites on the rGO promote adsorption, which is then followed by degradation through the metal oxides. Overall, the results unveil that the microwave-assisted synthesis of ZnO-TiO2-rGO nanocomposite is a promising and environmentally friendly approach for efficiently degrading dyes from contaminated wastewater using both UV light and natural sunlight irradiation.